The Role of The Technical Implementation Officer In The Community-Based Drinking Water And Sanitation Program (PAMSIMAS) In The Village of Suka Maju, Penarik Subdistrict, Mukomuko Regency - Pryandy, Reza; Kamil, Insannul (Peneliti.net, 2023)
The Pamsimas Development, which is one of the government programs aimed at improving access to drinking water and sanitation, is funded by the state budget (APBN) allocated to specific regions. Implemented since 2008, Pamsimas has had a positive impact on communities spread across villages and urban areas, particularly in meeting the needs for drinking water, sanitation, and promoting changes in health behavior. Currently, Pamsimas is a flagship program for the development of drinking water and sanitation supply systems in rural and urban areas, with the goal of increasing the number of residents who can access drinking water and sanitation services, enhancing the adoption of clean and healthy living values, and achieving 100% access to drinking water and sanitation by 2024. Pamsimas is considered a strategic step in improving community access to drinking water and sanitation, with a community-based approach to empowerment and sustainability being the key to its success. The role of the Technical Implementation Unit Head (PPTK) is crucial in maintaining the quality and success of the PAMSIMAS program. Close collaboration with relevant parties, local governments, and the community is essential to achieving program goals effectively. In the implementation of PAMSIMAS development, there are often discrepancies between the proposed plans and the actual implementation, requiring the role of the Technical Implementation Unit Head (PPTK) in rationalizing planning outcomes for the implementation of PAMSIMAS development. Additionally, PPTK plays a role in resolving and finding solutions to conflicts within the community during the implementation of self-management PAMSIMAS.